THE ROLE AND ROLE OF ADAPTATION IN THE WORK OF A MODERN TEACHER - Nishonov Nodirbek Alimjanovich; Turgunov Bahrom Rakhimjonovich (Galaxy International Interdisciplinary Research Journal, 2021)
This article analyzes the process of school adaptation of teachers working in educational institutions on the example of different ages. There is also talk of the teacher’s adaptation to the latest developments in education.